Social Justice and Social and Emotional Learning in the Classroom - Pereira, Monica; Lomax, Danna; Veldman, Brittnee (Allies for Education, 2020)
Learners of all ages are encouraged to interrogate institutions that frame their lives through the Teaching Tolerance Social Justice Standards (SJS) and the five competencies of Social and Emotional Learning (SEL). The SJS and SEL used in classroom and community work cultivate self-awareness, relationship-building, and responsible decision-making. They can instigate actionable outcomes that contribute to social justice initiatives and help to sustain a democratic society. This paper describes a presentation of the use of SJS and SEL with a short book and an activity to demonstrate how this may be done.